A study of Aarong social compliance and producer development (SCPD) and its role in encouraging its existing, next generation and declining producer to maintain export quality products - Tuz Zahra, Fatema (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.